The Effect of a Yoga Program on "Health-Related Quality of Life" of Children in Residential Care Centers - Lal kheirkhah, Elahe; Nourian, Manijeh; Saatchi, Kiarash; Ahmadi, Farzane (Advances in Nursing & Midwifery, 2018)
Abstract Introduction: Children living in residential care centers are a vulnerable population and have a lower Health-Related Quality of Life (HRQOL). This study explored a yoga exercise program on HRQOL in children living in residential care centers. Methods: In this quasi-experimental, one group before-after study with time series design, all children aged 8 to 13 years, who qualified for the inclusion criteria and were living in governmental residential care centers of Isfarayen were selected, using the census method. The participants took part in yoga classes for 8 weeks. The HRQOL was assessed using Kids Screen Health-related Quality of Life Questionnaire (KS-HRQOLQ). The gleaned data were analyzed with SPSS21 using repeated measurements analysis. Results: Changes in the total score of HRQOL obtained in five measurements were not statistically significant (P = 0.270). Variations in the score of HRQOL in the dimensions of "mental well-being", "the relations with parents and self-autonomy", "social support and peers", and "school environment" were not significant before to one month after completion of interventions (P = 0.29, P = 0.67, P = 0.16, P = 0.50, respectively). For the physical well-being dimension, the changes were significant frombefore to immediately after completion of interventions (P = 0.013). Changes were not significant in the presence of personal and demographic variables (P = 0.45, P > 0.05). Conclusions: This study indicated that yoga increases life quality only in the physical well-being dimension. Given that life quality reflects the wishes, expectations, and hopes of children and teenagers in relation to their present and future life and this feeling is time-related, culture-dependent, and context-oriented, it appears that life conditions of children in the current study and chronic continuous tension present in residential care centers probably made the effects of yoga different.